Pandora’s Box in the Deep Sea –Intraspecific Diversity Patterns and Distribution of Two Congeneric Scavenging Amphipods - Jażdżewska, Anna M.; Horton, Tammy; Hendrycks, Ed; Mamos, Tomasz; Driskell, Amy C.; Brix, Saskia; Arbizu, Pedro Martínez (Frontiers in Marine Science, 2021)
Paralicella tenuipes Chevreux, 1908 and Paralicella caperesca Shulenberger & Barnard, 1976 are known as widely distributed deep-sea scavenging amphipods. Some recent studies based on genetic data indicated the presence of high intraspecific variation of P. caperesca suggesting it is a species complex. Based on published molecular data from the Pacific and Indian oceans and new material obtained from North and South Atlantic, we integrated the knowledge on the intraspecific variation and species distribution of the two nominal taxa. The study included analysis of three genes (COI, 16S rRNA, 28S rRNA) and revealed the existence of a single Molecular Operational Taxonomic Unit (MOTU) within P. tenuipes and six different MOTUs forming P. caperesca. The distribution pattern of the recognized lineages varied with three (P. tenuipes, MOTU 1 and MOTU 5 of P. caperesca) being widely distributed. There was evidence of contemporary population connectivity expressed by the share of the same COI haplotypes by individuals from very distant localities. At the same time no signal of recent demographic changes was observed within the studied taxa. The time-calibrated phylogeny suggested the emergence of species to be at the time of Mesozoic/Cenozoic transition that may be associated with global changes of the ocean circulation and deep sea water cooling.